THE JÂNIO QUADROS'S GOVERNMENT THROUGH THE PAGES OF THE NEWSPAPER CALLED ÚLTIMA HORA (UH) - Fidelis, Thiago (Revista de Historia Social y de las Mentalidades, 2021)
In 1960, Jânio Quadros was elected president of the Republic. By this time, he was not linked to any major Political Party and, despite of this, had had successive electoral victories. Regarding the main circulation newspapers in the country, although many of them considered his rise a little suspicion, they ended up supporting him in the election. However, the newspaper called Ultima Hora (UH) did not legitimize the candidacy and remained faithful to the political labor culture, opposed to the bases that Quadros used to defend. Thus, this article aims to analyze how this communication mean portrayed Jânio Quadros's government, from his inauguration in January 1961 until his resignation, less than seven months later.
Keywords: Jânio Quadros; Last hour; Independent Foreign Policy; History of the press